A Quantitative Approach to the Russian Past: A Comment on "European Statistics, Russian Numbers and Social Dynamics, 1861–1914" by Alessandro Stanziani. Issue 1 (2nd May 2017) - Markevich, Andrei; Zhuravskaya, Ekaterina
Abstract : Alessandro Stanziani's article re-launches the discussion about the quality of Russian imperial statistics and the relevance of quantitative analysis for historical research at an important moment for Russia's economic history, when a lot of new data are being compiled and used by scholars. Similar productive discussions took place at other critical junctions for the fields of history, economics, political science, and other social sciences. For example, Robert Fogel's and Stanley Engerman's "Time on the Cross" (1974) triggered a profound discussion of potential benefits and limitations of quantitative approach to studying the history of the United States. The punch line of that discussion can be illustrated by the justification of the 1993 Nobel Prize in economics dedicated to Fogel "for having renewed research in economic history by applying economic theory and quantitative methods in order to explain economic and institutional change." In the context of Russian history, similar discussions took place in the Soviet Union in the 1970s between Ivan Koval'chenko and Boris Litvak and then later in this journal in the 1990s.